Computed Tomography and Biomechanical Comparison between Trans-Articular Screw Fixation and 2 Polymethylmethacrylate Cemented Constructs for Ventral Atlantoaxial Stabilization - Leblond, Guillaume; Moens, Noël M. M.; Gaitero, Luis; zur Linden, Alex; James, Fiona M. K.; Monteith, Gabrielle; Runciman, Robert J. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives Canine ventral atlantoaxial stabilization methods have been constantly evolving over the past few decades. Yet, proper experimental data comparing the feasibility and biomechanical properties of currently available surgical options are lacking. The aims of this study were (1) to describe and compare the safety profiles and biomechanical properties of three ventral atlantoaxial stabilization methods; and (2) to test whether recently reported optimal implant definitions constitute reasonable guidelines.Methods Three types of atlantoaxial stabilization including trans-articular screw fixation (TSF) and two cemented constructs (MI5 and MI6) were performed in 21 Beagle cadavers. Post-surgical computed tomography (CT) images of the constructs and biomechanical data were then generated and statistically analysed.Results The CT data revealed that TSF achieved significantly better apposition than cemented constructs. Out of 91 screws positioned, 4.4% were graded as dangerous and 86.8% as optimal. Optimal positioning was most challenging to obtain for mono-cortical screws. Analysis of biomechanical data suggested that all three techniques could likely achieve similar rates of atlantoaxial fusion when submitted to physiological loads but also that cemented constructs were less prone to failure compared with TSF.Clinical Significance This study provides evidence that all three techniques are technically feasible and biomechanically viable but also that the evaluated surgical guidelines could be improved.
Keywords: atlantoaxial instability; dogs; computed tomography; biomechanics; spine surgery